Can we identify patients at risk of life‐threatening allergic reactions to food?. Issue 9 (1st June 2016) - Turner, P. J.; Baumert, J. L.; Beyer, K.; Boyle, R. J.; Chan, C.‐H.; Clark, A. T.; Crevel, R. W. R.; DunnGalvin, A.; Fernández‐Rivas, M.; Gowland, M. H.; Grabenhenrich, L.; Hardy, S.; et al.
Abstract: Anaphylaxis has been defined as a 'severe, life‐threatening generalized or systemic hypersensitivity reaction'. However, data indicate that the vast majority of food‐triggered anaphylactic reactions are not life‐threatening. Nonetheless, severe life‐threatening reactions do occur and are unpredictable. We discuss the concepts surrounding perceptions of severe, life‐threatening allergic reactions to food by different stakeholders, with particular reference to the inclusion of clinical severity as a factor in allergy and allergen risk management. We review the evidence regarding factors that might be used to identify those at most risk of severe allergic reactions to food, and the consequences of misinformation in this regard. For example, a significant proportion of food‐allergic children also have asthma, yet almost none will experience a fatal food‐allergic reaction; asthma is not, in itself, a strong predictor for fatal anaphylaxis. The relationship between dose of allergen exposure and symptom severity is unclear. While dose appears to be a risk factor in at least a subgroup of patients, studies report that individuals with prior anaphylaxis do not have a lower eliciting dose than those reporting previous mild reactions. It is therefore important to consider severity and sensitivity as separate factors, as a highly sensitive individual will not necessarily experience severe symptoms during an allergic reaction. We identify the knowledge gaps that need to be addressed to improve our ability to better identify those most at risk of severe food‐induced allergic reactions.